Capitalism in the Digital Age and Education: Democracy, State, and Ideology (Revista Lusófona de Educação, 2024)
The aim of the article is to defend a theoretical-conceptual and analytical framework regarding the notionsof democracy, state, and ideology to analyze some of the advances of contemporary capitalism in its digital era within global education policy. The analytical procedure is based on a critical literature review on democracy, state, and ideology, focusing on the contexts of educational policy in Portugal and Brazil, framed within three periods of cyclical capitalist crises. The first section focuses on democracy, starting from the Carnation Revolution of 1974 (Portugal) and the end of the civic-military dictatorship in 1985 (Brazil). The second section centers on the state following the capitalist crisis of 2008. The third section addresses ideology in the context of the Covid-19 crisis. The results and conclusions focus on defending and advocating three central aspects for analyzing contemporary capitalism in its digital era. Firstly, studying democracy as a process of historical construction. Secondly, examining the contemporary State as a social relation through the analysis of governance networks and the relationship between the public and the private spheres. Thirdly, analyzing the existing ideology in the present and future configuration of educational reforms through the notions of sociotechnical imaginaries and technosolutionism.Keywords: digital capitalism; education policy; democracy; privatization; sociotechnical imaginaries